The Routledge handbook of chinese language and culture - Jiao, Liwei (Routledge language handbooks, 2024)
The Routledge Handbook of Chinese Language and Culture represents the first English anthology that delves into the fascinating and thought-provoking relationship between the Chinese language and culture, exploring various macro and micro perspectives.Chinese culture boasts a history of ten thousand years, while the Chinese language’s recorded history spans at least three thousand years, dating back to the Shang dynasty oracle bone inscriptions (OBI).This handbook is comprised of 17 chapters from 18 scholars including Victor Mair and William S-Y. Wang. Many chapters approach their respective topics with a comprehensive and historical outlook. Certain extensive subjects are addressed in multiple chapters, complementing one another. These topics include:- The languages and peoples of China, and the southern Chinese dialects- Mandarin’s evolution into a national language and its related writing reforms- Language as a propaganda tool in the Cultural Revolution and in contemporary China- Chinese idioms and colloquialismsThis book offers an approachable exploration of the subject, appealing to both specialists and enthusiasts of the Chinese language and culture